Assessment of Rwandan diabetic patients' needs and expectations to develop their first diabetes self-management smartphone application (Kir'App). (April 2019) - Kabeza, Claudine B.; Harst, Lorenz; Schwarz, Peter E. H.; Timpel, Patrick
Background: Knowledge of and coping with diabetes is still poor in some communities in Rwanda. While smartphone applications (or apps) have demonstrated improving diabetes self-care, there is no current study on the use of smartphones in the self-management of diabetes in Rwanda. Methods: The main objective of this study was to assess the needs and expectations of Rwandan diabetic patients for mobile-health-supported diabetes self-management in order to develop a patient-centred smartphone application (Kir'App). Results: Convenience sampling was used to recruit study participants at the Rwanda Diabetes Association. Twenty-one patients participated in semi-structured, in-depth, face-to-face interviews. Thematic analysis was performed using Mayring's method of qualitative content analysis. Conclusions: The study included 21 participants with either type 1 (female = 5, male = 6) or type 2 (female = 6, male = 4) diabetes. Participants' age ranged from 18 to 69 years with a mean age of 35 and 29 years, respectively. Eight main themes were identified. These were (a) diabetes education and desired information provision; (b) lack of diabetes knowledge and awareness; (c) need for information in crisis situations; (d) required monitoring and reminder functions; (e) information on nutrition and alcohol consumption; (f) information on physical activity; (g) coping with burden of disease, through social support and network; (h) app features. This study provides recommendations that will be used to design the features of the first Rwandan diabetes self-management smartphone application (Kir'App). The future impact of the application on the Rwandan diabetic patients' self-management capacity and quality of life will be evaluated afterwards.